Iron and Zinc Determination in Dietary Supplements by Flame Atomic Absorption Spectrophotometry - Sabriye Aydinoglu (Brazilian Journal of Pharmaceutical Sciences, 2023)
Abstract Recent studies have demonstrated that 30% of the world’s population suffers of anemia, half of the cases are related to iron deficiency, and the most common treatment is the use of iron supplementation. In this framework, the iron and zinc determination from different dietary supplements was performed by flame atomic absorption spectrophotometry. Concerning the dissolution of supplements, direct acid dissolution, wet digestion, and microwave digestion (MW) techniques were used for sample preparation. The iron and zinc recovery results demonstrated that the MW technique was the most appropriate for all of the supplements with the highest metal recovery yields. Moreover, the method validation parameters referred to a linear range for iron of 0.1-4 mg L-1 with a regression coefficient (R2) of 0.9998 ± 0.002, while for zinc it was 0.01-1 mg L-1 (R2 = 0.9997 ± 0.003). The limit of detection and quantification values were calculated as 0.03 and 0.09 mg L-1 for iron and 0.01 and 0.02 mg L-1 for zinc, respectively. The accuracy of the method was evaluated from the % recovery yield for iron and zinc, which, respectively, resulted in an oscillate of 99.2% to 102%, and 99.4% to 100.4% for the dietary investigated supplements. The precision of the method was determined by intra-day and inter-day precision with a relative standard deviation that was <2.0%.